Pengaruh Penggunaan jenis base makeup pada kulit kering terhadap hasil international bridal makeup - suwandipta, Julyannisa rizqyka; Octaverina Kecvara Pritasari; Maspiyah; Nieke Andina Wijaya (Program Studi Pendidikan Tata Rias, 2025)
A common issue in applying base makeup on dry skin is the skin’s tendency to lose moisture easily, leading to cracked makeup if inappropriate products are used. This study aims to analyze the effect of using gel and stick base makeup types on dry skin for international bridal makeup results. The research focuses include: 1) the makeup results on dry skin using gel-based makeup, 2) the makeup results on dry skin using stick-based makeup, and 3) the differences in the makeup results on dry skin between gel-based and stick-based makeup. This study employs a quantitative method with a true-experimental approach. Gel and stick base makeup were applied to models with dry skin, and the results were evaluated by 30 respondents consisting of lecturers, makeup artists (MUAs), and cosmetology students who had taken bridal makeup courses. Assessments were conducted using observation sheets. The results indicate that: 1) the use of gel-based makeup received an average score of 3.02, categorized as good; 2) the use of stick-based makeup received an average score of 2.66, also categorized as good; and 3) there is a significant difference in the international bridal makeup results on dry skin between the use of gel-based and stick-based makeup, with a significance value of 0.000 < 0.05. The conclusion of this study is that both types of base makeup can be used on dry skin, but gel-based makeup provides superior results compared to stick-based makeup. Keywords: Base makeup, Dry Skin, International Bridal makeup, Gel-Based makeup, Stick-Based makeup